Development of Chinese College English Teachers’ Psychological Empowerment Scale: A Validation Study - Lei, Pengfei; Xu, Jinfen (Frontiers in Psychology, 2022)
Relevant research shows teachers' "psychological power" plays a more essential role in promoting their professional development compared with the powers provided by various external factors, and it is therefore held that exploring college English teachers' individual psychological power is of great significance. To this end, this study investigated college English teachers’ psychological empowerment (CETPE) via the development and validation of CETPE’s scale. Based on our literature review on psychological empowerment and analysis of teachers professional development’s status quo, we made a working definition of CETPE as a system involving perception of their occupation, sense of competence, experiencing of autonomy, judgment of their impact and understanding of their status. In our study, firstly the literature review and the interview with 17 college English teachers were adopted to conceptualize the dimensions of CETPE, and an exploratory factor analysis of data was conducted from 227 college English teachers and then the subsequent confirmatory factor analysis of data collected from another sample of 1030 generated 15 items belonging to five factors. The findings reveal that CETPE is systematically composed of teachers’ positive perception and experience of work meaningfulness, teaching autonomy, occupational competence, professional impact and social status. This study provides a new path for teachers' professional development via strengthening their intrinsic driving force and thus helps improve the college English teaching effects.